Analisis Pengakuan Biaya Berdasarkan Standar Akuntansi Keuangan dan Undang-Undang Perpajakan Dalam Penentuan Pajak Penghasilan Badan Terutang Pada CV Setia Kawan Abadi - Kukuh Pangesti, Shalma; Natrion; Rachmawati, Budi (Mulia Pratama, 2024)
One of the largest state revenues is taxes. The amount of Corporate Income Tax is influenced by the costs that can be charged. Costs related to business activities are costs that are allowed to be charged in calculating Income Tax. This research was conducted at CV. Setia Kawan Abadi which is located at tpk. Ujung Menteng, Jl. Raya Bekasi no. Km.26, RT.1/RW.3, Cakung, City of East Jakarta. The research was carried out from March 2023 to May 2023. The sample in this study was the financial statements of CV. Setia Kawan Abadi in 2019 and 2020. There are differences in costs caused by the recognition of costs based on Financial Accounting Standards and the Tax Law. This study aims to find out how much the costs are based on Financial Accounting Standards in determining Corporate Income Tax Payable, how much costs are based on the Tax Law in determining Corporate Income Tax Payable and what is the comparison of cost recognition based on Financial Accounting Standards and the Tax Law in determining Tax Debt Agency Income. The data source used in this research is secondary data, namely data obtained from the company directly. The data collection techniques used are quantitative analysis and descriptive analysis. The results of this study are that costs are very influential in determining corporate income tax payable. Costs based on the 2019 Financial Accounting Standards are Rp. 2,763,770,349 while in 2020 it is Rp. 2,331,715,773. Costs based on the 2019 Tax Law amount to IDR 2,725,177,681 and in 2020 IDR. 2,308,979,191. The difference in costs based on the Financial Accounting Standards and the Tax Law in 2019 is Rp. 38,592,668 while the difference in 2020 is Rp. 22,736,582. The 2019 income tax payable is IDR 59,776,194 and the 2020 income tax is IDR 45,158,265. Thus it can be concluded that the greater the costs that can be charged, the smaller the Income Tax Payable, and vice versa.